2002
DOI: 10.2190/e68q-kw1g-jk5b-ttrm
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Web-Based Resources in Higher Education

Abstract: Recent increases in the use of Web-based resources by faculty in higher education appear to be reaching a plateau. To better understand how to encourage the use of Web resources a survey was designed to examine faculty perceptions about the navigability and content of a specific Web-based resource and their attitudes about the instructional use of Web-based resources in general. Results of the survey indicated that faculty with more years of experience and those teaching at research and doctoral institutions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Several recent reports on perceptions of faculty toward Web-based technology in higher education have appeared (e.g., [13,14]). The findings seem to indicate that gender plays a critical role in studies on faculty attitudes toward online teaching (see [15]).…”
Section: Attitudes and Use By Facultymentioning
confidence: 99%
“…Several recent reports on perceptions of faculty toward Web-based technology in higher education have appeared (e.g., [13,14]). The findings seem to indicate that gender plays a critical role in studies on faculty attitudes toward online teaching (see [15]).…”
Section: Attitudes and Use By Facultymentioning
confidence: 99%
“…In an earlier comprehensive study, Crooks, Yang and Duemer (2003) have examined the effects of various demographic factors on academics' perceptions of specific resources and their attitudes to the web-based instructional resources in the United States. Based on Multivariate Analysis of Variance (MANOVA), the study found that experienced academics displayed favourable attitudes toward the web resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the literature looking at the implementation ofWBIT focuses on faculty technology usage, faculty attitudes and concerns regarding the use of technology, and faculty perceptions toward the incorporation of technology into instruction (Aust, Newberry, O'Brien, & Thomas, 2005;Crooks, Yang, & Duemer, 2002;Inman & Mayes, 1998;Vodanovich & Piotrowski, 2005). Conversely, empirical research that examines institutional support concerning technology implementation in higher education has received significantly less attention.…”
Section: Distribution Of Computer Self-efficacy (Cse)mentioning
confidence: 99%